Penerapan Konseling Kelompok Untuk Menurunkan Prokrastinasi Akademik Pada Remaja - rivanda, sonyalita bintang (Pusat Riset dan Inovasi Nasional, 2022)
The academic procrastination can be defined as the procrastinating behavior of school assignment, so it can cause negative effects for individual. The negative effects of academic procrastination is the emergence of emotional not quite so well, such as feeling worried, desperate, and easily stressed. Group counseling is a dynamic interpersonal relationship between counselor and counselee focused on a joint problem-solving. The purpose of this research is can be the academic procrastination in adolescents using group counseling.This research uses quasi experimental method with pre test post test control group design and assisted by using a measuring instrument academic procrastination scale. In this research, sampling using purposive sampling.The sample of the research consisted of 16 adolescents and divided into two groups, eight teenagers to the experimental group and 8 teenagers to the control group. The results showed a significant difference in the level of the academic procrastination (Z = -3371; P 0.001 <0.05). Thus, it can be concluded that the application of group counseling can lower the academic procrastination in adolescents. Keywords: Academic Procrastination, group counseling